1988
DOI: 10.1111/j.1943-278x.1988.tb00148.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Survivors of Suicide and Accidental Death: Consequences for Widows

Abstract: The impact of completed suicide on the surviving family was studied. Thirteen widows whose husbands had died through suicide were compared with 13 widows whose husbands had died in accidents. The widows' views of their families' functioning, and the extent of life stress and psychiatric symptoms experienced by the widows, were assessed. Interview data suggested more guilt and blaming in suicide survivor families. However, on standardized questionnaires, suicide survivors showed no more family dysfunction, life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 10 publications
2
30
0
2
Order By: Relevance
“…These authors also report that survivors were the only group that reported lying to others about the cause of death (44% of subjects). Other studies report similar findings (Bailley et al, 1999; McNiel et al, 1988), including the observation that suicide survivors received significantly less emotional support than natural death survivors for their feelings of depression and grief, and confided less in members of their social networks (Farberow, Gallagher‐Thompson, Gilewski, & Thompson, 1992). Wagner and Calhoun (1991–1992) and Cleiren (1993) did not find quantitative differences in the perception of support, though the qualitative (i.e., interview) data of the former suggested that survivors felt pressure to recover faster and that only other survivors could actually understand their experience.…”
Section: Social Processes Surrounding Suicide Survivorsmentioning
confidence: 65%
See 1 more Smart Citation
“…These authors also report that survivors were the only group that reported lying to others about the cause of death (44% of subjects). Other studies report similar findings (Bailley et al, 1999; McNiel et al, 1988), including the observation that suicide survivors received significantly less emotional support than natural death survivors for their feelings of depression and grief, and confided less in members of their social networks (Farberow, Gallagher‐Thompson, Gilewski, & Thompson, 1992). Wagner and Calhoun (1991–1992) and Cleiren (1993) did not find quantitative differences in the perception of support, though the qualitative (i.e., interview) data of the former suggested that survivors felt pressure to recover faster and that only other survivors could actually understand their experience.…”
Section: Social Processes Surrounding Suicide Survivorsmentioning
confidence: 65%
“…Because suicide is self‐inflicted and violates the fundamental norms of self‐preservation, survivors often struggle to make sense of the motives and frame of mind of the deceased. Second, survivors show higher levels of feelings of guilt, blame, and responsibility for the death than other mourners (“Why didn't I prevent it?”) (Cleiren, 1993; Demi, 1984; Kovarsky, 1989; McNiel, Hatcher, & Reubin, 1988; Miles & Demi, 1991–1992; Reed & Greenwald, 1991; Silverman et al, 1994–1995). Occasionally, survivors feel that they directly caused the death through mistreatment or abandonment of the deceased.…”
Section: Thematic Aspects Of Suicide Bereavementmentioning
confidence: 99%
“…Most discussions of suicide stigmatization imply that the suicide survivor is likely to be subjected to greater social isolation and stigma than other survivors, such as accidental death survivors and survivors of untimely natural deaths. Yet, two early studies yielded results somewhat inconsistent with this expectation (Cleiren, Diekstra, Kerkhof, & van der Wal, 1994;McNiel, Hatcher, & Reubin, 1988).…”
mentioning
confidence: 92%
“…Beyond that, however, they are distinguishable emotions with distinct etiologies, distinct impacts on the development and maintenance of posttraumatic outcomes, and separate implications for treatment (Ferguson, Stegge, Miller, & Olsen, 1999;Tangney, 1999). Guilt and shame have been reported by survivors of many kinds of traumatic events, such as childhood sexual abuse (Spaccarelli, 1994), physical abuse (Brown & Kolko, 1999;Loader, 1998), serious accidents and burns (Kiecolt-Glaser & Williams, 1987), technological disasters (Joseph, Hodgkinson, Yule, & Williams, 1993), the death of a loved one (McNeil, Hatcher, & Reubin, 1988), violent crime (Andrews, Brewin, Rose, & Kirk, 2000), and war (Leskela, Dieperink, & Thuras, 2002). Trauma survivors frequently report feeling both guilt and shame regarding the same incidents (Hoglund & Nicholas, 1995;Kubany & Watson, 2003).…”
Section: The Nature Of Guilt and Its Relationship To Traumamentioning
confidence: 97%